An institutional approach to the management of the 'Can't Intubate, Can't Oxygenate' emergency in children. Issue 8 (9th June 2016) - Sabato, Stefano C.; Long, Elliot
Summary: The 'Can't Intubate Can't Oxygenate' emergency is rare in children. Nevertheless, airway clinicians involved in pediatric airway management must be able to rescue the airway percutaneously through the front of the neck should this situation be encountered. Little evidence exists in children to guide rescue techniques, and extrapolation of adult evidence may be problematic due to anatomical differences. This document reviews the currently available evidence, and presents a practical approach to standardizing equipment, techniques, and training for managing the 'Can't Intubate Can't Oxygenate' emergency in children.